Evaluation of Operation Patterns and Ship Needs on the Paciran-Bawean Crossing Route, East Java Province - Casmudi, Adi; Sidharta, Driaskoro Budi; Suharli, Ikka; Dalimunte, Irham Hasahatan; Hakiyah, Annida (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
KMP. Gili Iyang which operates on the Paciran-Bawean route has 2 trips/week with a crossing distance of 80 miles. However, the operation of ships on long distances is not balanced with the ideal number of trips, resulting in a buildup of vehicles and passengers at Paciran Port. Where the time needed to sail is 8 hours. Therefore, this research aims to determine the frequency, number of ships needed and efficient ship operation patterns according to the needs of service users. The analysis in this research includes load factor analysis, passenger and vehicle growth prediction analysis, ship frequency analysis, ship number requirement analysis, and scheduling analysis. From this analysis, it was concluded that the ideal number of ship frequencies on the Paciran-Bawean route is 1 trip/week, and the number of ships that must be operated is 1 ship, and the results of the analysis show that the schedule for ships serving the Paciran-Bawean route is still not yet in accordance. So rescheduling is needed from 2 trips/week to 1 trip/week and forecasting is needed for the next 5 years so that the number of trips is in accordance with the needs of service users, as well as the operation of the KMP. Dharma Kencana on the Paciran- Bawean route so that there is a balance between service users and service providers.